2019
DOI: 10.1242/jcs.233783
|View full text |Cite
|
Sign up to set email alerts
|

Condensin II protein dysfunction impacts mitochondrial respiration and stress response

Abstract: The maintenance of mitochondrial respiratory function and homeostasis is essential to human health. Here, we identify condensin II subunits as novel regulators of mitochondrial respiration and mitochondrial stress responses. Condensin II is present in the nucleus and cytoplasm. While the effects of condensin II depletion on nuclear genome organization are well studied, the effects on essential cytoplasmic and metabolic processes are not as well understood. Excitingly, we observe that condensin II chromosome-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 103 publications
0
4
0
Order By: Relevance
“…It has been suggested in the literature that subunits of condensing I and condensin II are associated with tumorigenesis [ 34 ]. Recently, studies have reported that NCAPD3 localizes to the exterior surface of mitochondria and affects mitochondrial oxidative stress responses [ 35 ]. The research on NCAPD3 mainly focuses on its role in condensation and segregation during cell division, little is known about its bio-functions and molecular mechanisms in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested in the literature that subunits of condensing I and condensin II are associated with tumorigenesis [ 34 ]. Recently, studies have reported that NCAPD3 localizes to the exterior surface of mitochondria and affects mitochondrial oxidative stress responses [ 35 ]. The research on NCAPD3 mainly focuses on its role in condensation and segregation during cell division, little is known about its bio-functions and molecular mechanisms in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer, NCAPD3 has also been shown to activate E2F1 and STAT3 and drive prostate cancer progression ( 73 ). In addition, NCAPD3 is present in the outer mitochondrial membrane and regulates oxidative stress in the mitochondria, which is not dependent on glycolysis and does not affect the number of mitochondria ( 74 ). Ultimately, in vitro experiments also confirmed that the knockdown of NCAPD3 resulted in a significant decrease in cell viability and colony number in BC cell lines MDA-MB-231 and BCAP-37 and a significant slowdown in scratch healing in MDA-MB-231 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Studies in thoroughbred horses have identified a candidate gene JAM3, involved in spermatogenesis in horses and genes CALR and DNMT1 mediating fertility and pregnancy in mares [48,49]. The dysfunction of Condensin II protein in humans affects mitochondrial respiration and mitochondrial oxidative stress response [50]. Other researchers have found that the PRDX2 gene plays a functional role in oxidative stress in equine species; JUNB, PIN1, and KANK2 genes are involved in repair processes in ligament and tendon injuries; and LDLR regulates lipid metabolism, which affects the risks of degenerative suspensory ligament desmitis disease [51].…”
Section: Discussionmentioning
confidence: 99%